New phase of MnSb2O6 prepared by ion exchange: structural, magnetic, and thermodynamic properties - Nalbandyan, Vladimir B.; Koo, Changhyun; Klingeler, Rüdiger (Inorganic chemistry, 2015)
A new layered trigonal (P3̅1m) form of MnSb2O6, isostructural with MSb2O6 (M = Cd, Ca, Sr, Pb, and Ba) and MAs2O6 (M = Mn, Co, Ni, and Pd), was prepared by ion-exchange reaction between ilmenite-type NaSbO3 and MnSO4-KCl-KBr melt at 470 °C. It is characterized by Rietveld analysis of the X-ray diffraction pattern, electron microprobe analysis, magnetic susceptibility, specific heat, and ESR measurements as well as by density functional theory calculations. MnSb2O6 is very similar to MnAs2O6 in the temperature dependence of their magnetic susceptibility and spin exchange interactions. The magnetic susceptibility and specific heat data show that MnSb2O6 undergoes a long-range antiferromagnetic order with Néel temperature TN = 8.5(5) K. In addition, a weak ferromagnetic component appears below T1 = 41.5(5) K. DFT+U implies that the main spin exchange interactions are antiferromagnetic, thereby forming spin-frustrated triangles. The long-range ordered magnetic structure of MnSb2O6 is predicted to be incommensurate as found for MnAs2O6. On heating, the new phase transforms to the stable P321 form via its intermediate disordered variant.
Gesehen am 10.08.2020